2006
DOI: 10.1254/jphs.fp0060862
|View full text |Cite
|
Sign up to set email alerts
|

Localized Expression of Histamine H1 Receptors in Syncytiotrophoblast Cells of Human Placenta

Abstract: Abstract. The previous Northern blot analysis and in situ hybridization studies showed that histamine H 1 -receptor (H 1 R) mRNA is expressed in human placenta and suggested that H 1 R plays some roles in the function of placenta in pregnancy. To investigate further, it is essential to show the precise location of H 1 R in the placenta. In the present study, we investigated H 1 R expression in human placenta by radioligand binding assay and immunohistochemical study using an antibody against human H 1 R. Place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Mean ( 8 standard error of the mean) histamine content of the myometrium has been reported as 2.1 8 0.3 g/g of tissue. With regard to the uteroplacental interface, Matsuyama et al [20] reported expression of H1R in human syncytiotrophoblast cells and Brew and Sullivan et al [31] reported H1R and H2R expressions in human decidua. However, the existence of histamine receptors in human amnion has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Mean ( 8 standard error of the mean) histamine content of the myometrium has been reported as 2.1 8 0.3 g/g of tissue. With regard to the uteroplacental interface, Matsuyama et al [20] reported expression of H1R in human syncytiotrophoblast cells and Brew and Sullivan et al [31] reported H1R and H2R expressions in human decidua. However, the existence of histamine receptors in human amnion has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of the samples was performed in the presence of trypan blue (200 g/ml) to quench extracellular fluorescence. (29). For saturation studies, increasing concentrations of [ 3 H]mepyramine, ranging from 0.01 to 15 nM, were incubated with 10 6 cells/tube, in the absence or presence of 10 M mepyramine, in a total volume of 100 l. After 40 min at 4°C, incubation was stopped by dilution with 3 ml of ice-cold 50 mM Tris-HCl (pH 7.4) and rapid filtration under reduced pressure onto Whatman GF/B glass-fiber filters, followed by three washes with 3 ml of ice-cold buffer.…”
Section: Phagocytosis Of Fitc-ova-coated Latex Beadsmentioning
confidence: 99%
“…The biologic mechanism through which antihistamines inhibit the actions of histamine may affect both implantation and uterine contraction. Histamine is a monoamine that impacts several cellular pathways in the female reproductive system, as it is produced by uterine mast cells, uterine epithelial cells, and the placenta . The action of histamine is mediated through four subtypes of histamine receptors: H1, H2, H3, and H4 receptors .…”
Section: Introductionmentioning
confidence: 99%
“…The action of histamine is mediated through four subtypes of histamine receptors: H1, H2, H3, and H4 receptors . Of particular interest are the H1 and H2 receptors, which are expressed in the uterus, placenta, and blastocysts . Stimulation of H1 receptors by agonists leads to smooth muscle contraction, nitric oxide formation for endothelial vasodilation, and increased vascular permeability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation